Perlindungan Konsumen Terhadap Kerugian Akibat Cacat Produk dan Tanggung Jawab Pelaku Usaha - Cecep Tedy Siswanto; Lucia Setyawahyuningtyas (Jurnal Hukum Caraka Justitia, 2026)
The increasing complexity of products on the market has implications for the potential for consumers to suffer losses due to product defects, particularly in situations where there is an imbalance in the legal relationship between consumers and businesses. This study examines the forms of legal protection available to consumers who suffer losses due to product defects, analyzes the concept and limitations of business liability, and assesses the relevance and effectiveness of applicable legal regulations. This study is a normative legal study with a legislative and conceptual approach in the field of civil law and consumer protection law. The results of the study show that normatively, the Civil Code and Law Number 8 of 1999 have provided sufficient protection through mechanisms of default, unlawful acts, and specific regulations regarding the obligations of business actors. However, the effectiveness of this protection is still hampered by the practice of standard clauses, limitations on compensation, the complexity of the distribution chain, and the weak enforcement of dispute resolution decisions. This study emphasizes the importance of strengthening the implementation and enforcement of the law to ensure that consumer protection against losses due to product defects is realized effectively and fairly.